Delayed medical care due to transportation barriers among US children with atopic dermatitis. Issue 6 (25th August 2022) - Zheng, David X.; Cwalina, Thomas B.; Mulligan, Kathleen M.; Gallo Marin, Benjamin; O'Connell, Katie A.; Shah, Sonal D.; Kwatra, Shawn G.; Mostaghimi, Arash
Abstract: Our objective was to examine the prevalence and predictors of delayed medical care due to transportation barriers among children with atopic dermatitis (AD) living in the United States (US). We analyzed data from the 1998–2018 National Health Interview Survey, a nationally representative survey of US households. In 2018, transport‐delayed care was reported for 3.4% of US children with AD, representing approximately 279, 000 children annually given the National Health Interview Survey's weighted survey design, and was more common among patients of lower socioeconomic status. Targeted interventions aimed at reducing transportation barriers to healthcare among at‐risk AD patients may reduce health disparities related to AD.